Changes in baroreceptor sensitivity after eversion carotid endarterectomy - Demirel, Serdar; Attigah, Nicolas; Macek, Laura; Hakimi, Maani; Able, Thomas; Böckler, Dittmar (Journal of vascular surgery, 2012)
Objective: Posteversion carotid endarterectomy hypertension has been suggested to be associated with impaired baroreceptor sensitivity (BRS), which has been identiﬁed as a factor of prognostic relevance in patients with cardiovascular disease. The aim of this prospective single-center nonrandomized study was to describe the changes of BRS in the early postoperative period after eversion carotid endarterectomy (E-CEA). Methods: Spontaneous BRS and hemodynamic parameters such as blood pressure (BP), heart rate (HR), cardiac output (CO), and total peripheral resistance (TPR) were evaluated preoperatively as well as postoperatively after 1 and 3 days using a noninvasive sequential cross-correlation method. Additionally, any modiﬁcation in vasoactive medication due to BP derangement in the postoperative period was noted. Due to non-normal distribution of BRS, HR, and TPR samples, all measured values were expressed as medians with interquartile range (IQR), and a nonparametric test (Friedman) was performed. After adjustment for multiple testing, differences were considered statistically signiﬁcant when the two-tailed P value was less than .0036. Results: Thirty-ﬁve patients (mean age, 71 years) with symptomatic or asymptomatic internal carotid artery stenosis were included. The BRS signiﬁcantly decreased to a lower level 24 hours after surgery (4.71 ms/mm Hg [3.02-6.1]) than preoperatively (5.95 ms/mm Hg [4.68-10.86]; P < .0001), resulting in a within-patient difference of -2.46 ms/mm Hg (95% conﬁdence interval [CI], - 8.38 - -1.52). This difference (95% CI, [- 1.58 (- 8.24 - - 0.80)]) persisted at the 72-hour measurements (5.63 ms/mm Hg [3.23-7.69]; P ؍ .0005). The HR, reﬂecting the sympathetic activity, increased 24 hours after the operation (69 bpm [61.3-77.7]) compared with preoperative values (63 bpm [57.9-73.2]; P ؍ .005) (within-patient difference [95% CI] 3.7 [1.5-8.5]), and this increase reached signiﬁcance at 72 hours (69 bpm [65.4-77.5]; P ؍ .001) (within-patient difference [95% CI] 5.5 [2.3-8.8]). Values of systolic pressure, diastolic pressure, mean arterial pressure, CO, and TPR were not signiﬁcantly different between pre- and postoperative measurements. Overall, 23 (66%) patients developed signiﬁcant postoperative hypertension requiring aggressive management with additional medications. Conclusions: E-CEA might have a decreasing inﬂuence on BRS, leading to increased sympathetic activity. Investigations of the longer-term effects of impaired BRS are warranted. These ﬁndings should be interpreted with caution, noting the limitation of an absent control group. ( J Vasc Surg 2012;55:1322-8.)